Analisis Gaya Belajar Peserta Didik pada Pembelajaran PPKn Kelas III SD Supriyadi Semarang - Atussilmi, Rifqi; Sulianto, Joko; Pramasdyahsari, Agnita Siska (ANWARUL, 2023)
Learning style is a way of learning from how students absorb, and then organize and process the information obtained from the learning process. There are three types of learning styles that will be discussed in this study, namely visual (tend to learn through what they see), auditory (learn through what they hear) and kinesthetic (learn through movement and touch). The purpose of this study was to determine the learning styles of students when learning Civics. The research method is qualitative research. Data collection techniques through interviews, observation and documentation. Data validity was carried out through technique and source triangulation. The data analysis technique used consists of data acquisition, data reduction, data presentation and drawing conclusions. The results showed that the learning styles of SD Supriyadi Semarang class students in mathematics learning, which showed visual characteristics had visual characteristics, namely students could understand problems by reading, which they themselves could not. The auditory learning style means that students understand better when the teacher reads the questions, knows how to convey information obtained from their work orally. A learning style with kinesthetic characteristics, namely students prefer to solve problems in groups, cannot concentrate on solving problems if they have to sit still for a long time. The results showed that the learning style of the 3rd grade students at SD Supriyadi Semarang was a learning style. visual, auditory, kinesthetic and the most dominant learning style is the visual learning style.